DAMPAK KONTRIBUSI PROGRAM BADAN USAHA MILIK DESA (BUMDes) PEMATANG JAYA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA PEMATANG BERANGAN - Bardansyah Ibrahim Rangkuti (Jurnal Ilmiah Cano Ekonomos, 2023)
Badan Usaha Milik Desa (BUMDes) are business entities whose capital is wholly or substantially owned by the village through direct participation originating from village assets which are separated to manage assets, service services and other businesses for the greatest possible welfare of the village community. By using quantitative research methods. In this study the authors used a questionnaire as a tool to collect data. The tests used were validity test, reliability test, normality test, simple linear regression analysis, coefficient of determination test (R2) and statistical t test with the help of SPSS version 23. The results of the partial test showed that the Badan Usaha Milik Desa (BUMDes) has a significant effect on increasing the welfare of the community in Pematang Berangan Village, Rambah District, Rokan Hulu Regency. This can be seen from the value of the t count > t table and the significant level is smaller than Alpha (0.05).